INKONSISTENSI PENERAPAN PRINSIP INDEPENDENSI KEKUASAAN KEHAKIMAN DALAM PELAKSANAAN SELEKSI CALON HAKIM - Azhar, Ikhsan (Veritas et Justitia, 2018)
The general public in 2017 hotly debated the implemented selection process of Judges. The focus is on the issue of government involvement in the selection process which potentially jeopardize the judiciary’s independence.  In discussing this particular issue, the author uses a juridical normative or dogmatic approach and other data is collected by the use of library research . In addition, the author also compares the existing policy and rules/regulation concerning judge selection from different government’ era (the Old & New Order). A number of conclusions can be drawn from this comparison, i.e. that during the Old dan New Order Government, the judiciary was never considered independent. The government on a regular basis intervene in the selection process, appointment and placement of judges and have a strong say in their professional carrer path.  In contrast, only after the fall of the New Order Government, did the Judiciary enjoy independence which is guaranteed by virtue of Law 35/1999 and the 1945 Constitution (amended version).  Unfortunately though the Supreme Court decide to bring back in the government in the selection process and in doing that jeopardize the judicary’s independence.